2017
DOI: 10.1155/2017/6071031
|View full text |Cite
|
Sign up to set email alerts
|

Recovery following Thyroxine Treatment Withdrawal, but Not Propylthiouracil, Averts In Vivo and Ex Vivo Thyroxine-Provoked Cardiac Complications in Adult FVB/N Mice

Abstract: Persistent cardiovascular pathology has been described in hyperthyroid patients even with effective antithyroid treatment. Here, we studied the effect of a well-known antithyroid drug, propylthiouracil (PTU; 20 mg/kg/day), on thyroxine (T4; 500 µg/kg/day)-induced increase in blood pressure (BP), cardiac hypertrophy, and altered responses of the contractile myocardium both in vivo and ex vivo after 2 weeks of treatment. Furthermore, the potential recovery through 2 weeks of T4 treatment discontinuation was also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
(128 reference statements)
1
6
0
Order By: Relevance
“…Since there was no significant difference in mean serum T3 level between apigenin and PTU-treated groups, other molecular mechanisms may contribute to the dissimilar results of both therapies on hyperthyroidism-induced LVH that need extra investigations. Consistent with our results regarding PTU therapy, common cardiovascular abnormalities accompanying hyperthyroidism persisted despite effective PTU antithyroid therapy in L-thyroxine induced hyperthyroidism in FVB/N male mice [69], in rats [70] and in patients with overt hyperthyroidism [71]. Concerning the effect of PTU on cardiac fibrosis, there is a common agreement on the association of hypothyroidism and cardiac fibrosis [67,72].…”
Section: Estimation Of Hyperthyroidism-associated Lvhsupporting
confidence: 90%
“…Since there was no significant difference in mean serum T3 level between apigenin and PTU-treated groups, other molecular mechanisms may contribute to the dissimilar results of both therapies on hyperthyroidism-induced LVH that need extra investigations. Consistent with our results regarding PTU therapy, common cardiovascular abnormalities accompanying hyperthyroidism persisted despite effective PTU antithyroid therapy in L-thyroxine induced hyperthyroidism in FVB/N male mice [69], in rats [70] and in patients with overt hyperthyroidism [71]. Concerning the effect of PTU on cardiac fibrosis, there is a common agreement on the association of hypothyroidism and cardiac fibrosis [67,72].…”
Section: Estimation Of Hyperthyroidism-associated Lvhsupporting
confidence: 90%
“…And they reported that these aforementioned patients could also have their cardiac function completely restored after total thyroidectomy ( Muthukumar et al, 2016 ). In fact, Saad et al have reported that treatment of the thyroid gland significantly prevented cardiac dysfunction in a mouse model of T4-induced cardiac dysfunction ( Saad et al, 2017 ). Furthermore, reversibility of heart disease was observed after 2 weeks of T4 treatment, including cardiac hypertrophy ( Saad et al, 2017 ).…”
Section: Hyperthyroidism and The Cardiovascular Systemmentioning
confidence: 99%
“…In fact, Saad et al have reported that treatment of the thyroid gland significantly prevented cardiac dysfunction in a mouse model of T4-induced cardiac dysfunction ( Saad et al, 2017 ). Furthermore, reversibility of heart disease was observed after 2 weeks of T4 treatment, including cardiac hypertrophy ( Saad et al, 2017 ).…”
Section: Hyperthyroidism and The Cardiovascular Systemmentioning
confidence: 99%
“…Supporting clinical findings, experimental data also demonstrated that antithyroid treatment significantly prevented the cardiac dysfunction induced by T4 in mice. In addition, the reversibility of cardiac pathology was also observed after 2 weeks of discontinuation of treatment with T4, including cardiac hypertrophy (53).…”
Section: Hyperthyroidism and The Heartmentioning
confidence: 95%